Copper-clad plate for high-frequency circuit, preparation method of copper-clad plate and organic dielectric slurry

By using industrial raw materials such as 1,2,4-trigensum cyclumane and di bromide, prepare a copper-covering plate with low-agency loss and high glass transformation temperature, solving the lack of heat resistance to existing materials at high temperature at high temperatures The problem realizes the dual optimization of the performance and cost of high -frequency circuits.

CN119369817AActive Publication Date: 2025-01-28SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411415250.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-28
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing high-frequency circuit copper clad materials are insufficient in heat resistance at high temperatures, with high dielectric loss and dielectric constant, which cannot meet the requirements of communications above 5G. At the same time, cost control is difficult to achieve low-cost production.

Method used

Industrial products 1,2,4-triaethyl cyclumane and di bromodramidine are used as raw materials. Organic pulp is prepared through specific process steps, and combined with glass fiber cloth and copper foil to prepare copper plates through thermal pressure system.

Benefits of technology

The prepared copper -covered plates have low dielectric loss, high glass transition temperature, and low thermal expansion coefficients. Various indicators meet the requirements of the use of high -frequency circuits, and the process is simple and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119369817A_ABST
    Figure CN119369817A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-clad plate for a high-frequency circuit, a preparation method of the copper-clad plate and organic dielectric paste. The preparation method comprises the following steps: adding a hydrogenated styrene-butadiene-styrene copolymer, an aryl-containing polyethylene cyclohexane derivative, silicon dioxide powder and dicumyl peroxide into an organic solvent, and stirring until the materials are completely dissolved to obtain organic medium slurry; soaking glass fiber cloth in the organic medium slurry until the glass fiber cloth is coated with the organic medium slurry to obtain a glass fiber cloth prepreg; and placing the multi-layer glass fiber cloth prepreg between two layers of copper foils, and carrying out hot pressing to obtain the copper-clad plate for the high-frequency circuit. The preparation method disclosed by the invention is simple in process and low in cost, the copper-clad plate is low in dielectric loss, high in glass-transition temperature and low in thermal expansion coefficient, and various indexes basically meet the use requirements of the copper-clad plate for a high-frequency circuit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper-clad laminates for high-frequency circuits, and in particular to copper-clad laminates for high-frequency circuits, a preparation method thereof, and organic dielectric slurry. Background Art

[0002] With the development of AI and autonomous driving, people have higher and higher requirements for data transmission and communication network speed. For example, the 6G technology currently under development will use terahertz (THz), that is, the submillimeter frequency band, and its transmission capacity will be 100 times higher than that of 5G. The higher the communication frequency, the higher the requirements for its printed circuit board PCB, which will mainly include lower dielectric loss Df, lower dielectric constant Dk, higher reliability, higher heat resistance and extremely low thermal expansion coefficient CTE. The most important of these is lower Df.

[0003] The manufacturing process of integrated circuits requires temperatures above 400 degrees, and the temperature required in the subsequent processing is even higher. The copper wiring process can be completed below 250 degrees if it is carried out by electroplating or chemical reduction, but in order to ensure that the copper deposition is dense and free of pores, annealing treatment is required at 400 to 450 degrees, so the material is required to have excellent heat resistance and a very high glass transition temperature. For example, the heat resistance of polyimide and polybenzoxazine can meet the requirements, but Dk and Df are too high to meet the requirements of communications above 5G. Bis(vinylbenzene)ethane (BVPE) is a hydrocarbon resin currently used in industry for curing copper clad laminates. Its glass transition temperature Tg is lower than 200°C, and its heat resistance needs to be improved.

[0004] In addition, due to the huge amount of circuit boards used, cost control of the resin used is very important. At this stage, only simple deep processing using industrial raw materials can meet the market's low-cost needs. Summary of the invention

[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a copper clad laminate for high-frequency circuits, using industrial products 1,2,4-trivinylcyclohexane and dibromoarene as raw materials to prepare an organic medium, with a simple process and low cost; the prepared copper clad laminate for high-frequency circuits has low dielectric loss Df, high glass transition temperature Tg, and low thermal expansion coefficient, and various indicators basically meet the use requirements of copper clad laminates for high-frequency circuits.

[0006] Another object of the present invention is to provide a copper clad laminate for high frequency circuits.

[0007] Another object of the present invention is to provide an organic dielectric slurry for preparing a copper-clad laminate for a high-frequency circuit.

[0008] Another object of the present invention is to provide a polyvinyl cyclohexane derivative containing an aromatic group for use in preparing a copper-clad laminate for a high-frequency circuit.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] The present invention provides a method for preparing a copper clad laminate for a high-frequency circuit, comprising the following steps:

[0011] 25-35 parts of hydrogenated styrene-butadiene-styrene copolymer, 65-75 parts of aromatic-containing polyvinyl cyclohexane derivatives, 15-25 parts of silicon dioxide powder, and 0.8-1.2 parts of dicumyl peroxide are added to an organic solvent and stirred until completely dissolved to obtain an organic medium slurry;

[0012] soaking the glass fiber cloth in the organic medium slurry until the glass fiber cloth is covered by the organic medium slurry to obtain the glass fiber cloth prepreg;

[0013] Multiple layers of glass fiber cloth prepreg are placed between two layers of copper foil, and after hot pressing, a copper clad laminate for high-frequency circuits is obtained;

[0014] Wherein, the aromatic-containing polyvinyl cyclohexane derivative has the following structure:

[0015]

[0016] wherein Ar is an aromatic hydrocarbon;

[0017] TVCH is triethylene cyclohexane, and its structure is one of the following structures:

[0018]

[0019] TVCH is connected to the aromatic hydrocarbon at the dotted line.

[0020] Preferably, the aromatic hydrocarbon is benzene, biphenyl, terphenyl, fluorene, naphthalene or anthracene.

[0021] Preferably, the aromatic hydrocarbon has one of the following structures:

[0022]

[0023] Preferably, the preparation of the aromatic-containing polyvinyl cyclohexane derivative is as follows:

[0024] Potassium phosphate, 1,2,4-trivinylcyclohexane, dibromoarene, N,N-dimethylformamide, palladium acetate and triphenylphosphine are added; the reaction is carried out at 120-140° C. for 20-48 hours in an argon atmosphere; the product is precipitated, centrifuged, dried, column-passed, and then spin-dried and pumped to dryness with an oil pump heated to 115-125° C., then recrystallized, and pumped at 75-85° C. in a vacuum drying oven with a diaphragm pump for 0.8-1.2 hours to obtain an aromatic-containing polyvinylcyclohexane derivative TVCH-Ar-TVCH.

[0025] Preferably, the molar ratio of the 1,2,4-trivinylcyclohexane to the dibromoarene is (1.8-2.2):1.

[0026] Preferably, the amount of palladium acetate added is 0.8-1.0% of the molar amount of dibromoarene; and the amount of triphenylphosphine added is 1%-5% of the molar amount of dibromoarene.

[0027] Preferably, the hot pressing is specifically: hot pressing under the conditions of 205-215° C. and 2.8-3.2 MPa.

[0028] The present invention also provides a copper-clad laminate for high-frequency circuits, which is prepared by the method for preparing the copper-clad laminate for high-frequency circuits.

[0029] The present invention also provides an organic medium slurry, which comprises the following components dissolved in an organic solvent, in parts by weight:

[0030]

[0031] Preferably, the peroxidation initiator is dicumyl peroxide;

[0032] The aromatic-containing polyvinyl cyclohexane derivative has the following structure:

[0033]

[0034] wherein Ar is an aromatic hydrocarbon;

[0035] TVCH is triethylene cyclohexane, and its structure is one of the following structures:

[0036]

[0037] TVCH is connected to the aromatic hydrocarbon at the dotted line.

[0038] The present invention also provides a polyvinyl cyclohexane derivative containing an aromatic group, which has the following structure:

[0039]

[0040] wherein Ar is an aromatic hydrocarbon;

[0041] TVCH is triethylene cyclohexane, and its structure is one of the following structures:

[0042]

[0043] TVCH is connected to the aromatic hydrocarbon at the dotted line.

[0044] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0045] (1) The method for preparing a copper-clad laminate for high-frequency circuits of the present invention uses industrial products 1,2,4-trivinylcyclohexane and dibromoaromatic hydrocarbons as raw materials to prepare the organic medium therein, and has a simple process and low cost.

[0046] (2) The copper clad laminate for high-frequency circuits of the present invention has a low dielectric constant, a dielectric loss Df at 10 GHz as low as 0.00101, a glass transition temperature Tg as high as 277° C., and a low thermal expansion coefficient. All indicators basically meet the use requirements of the copper clad laminate.

[0047] (3) The copper-clad laminate for high-frequency circuits of the present invention has stable dielectric properties, and the dielectric loss increases by only 4% after working for 1 hour, and remains unchanged for 1-24 hours. However, the dielectric loss of diphenylethylene ethane BVPE with the best performance currently increases by 6.3% after 1 hour, and continues to increase by 7.6% for 1-24 hours, with a total increase of 13.9%.

[0048] (4) The aromatic-containing polyvinyl cyclohexane derivatives of the present invention are all-carbon-hydrogen structures and have extremely low Dk and Df. They contain benzene rings and have higher heat resistance than all-fatty / alicyclic compounds.

[0049] (5) The aromatic-containing polyvinyl cyclohexane derivative of the present invention contains at least four vinyl functional groups and is asymmetric, so that a higher degree of crosslinking can be obtained by thermal curing, thereby having higher dielectric properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 This is the NMR spectrum of the phenyl-containing polyvinylcyclohexane derivative TVCH-Ph-TVCH of Example 1 of the present invention.

[0051] Figure 2 The test results of DMA (dynamic mechanical analysis) for the thermal stability of the copper clad laminate of Example 1 of the present invention are as follows; the blue curve in the figure represents the storage modulus; the green curve represents the loss modulus; and the red curve represents the loss tangent.

[0052] Figure 3 The thermal stability of the copper clad laminate of Example 1 of the present invention is tested using TMA (thermomechanical analysis).

[0053] Figure 4 This is the thermogravimetric analysis test result of the phenyl-containing polyvinylcyclohexane derivative TVCH-Ph-TVCH of Example 1 of the present invention.

[0054] Figure 5 This is the NMR spectrum of the phenyl-containing polyvinylcyclohexane derivative TVCH-BP-TVCH of Example 2 of the present invention.

[0055] Figure 6 The test results of DMA (dynamic mechanical analysis) for the thermal stability of the copper clad laminate of Example 2 of the present invention are as follows; the blue curve in the figure represents the storage modulus; the green curve represents the loss modulus; and the red curve represents the loss tangent.

[0056] Figure 7 The thermal stability of the copper clad laminate of Example 2 of the present invention is tested using TMA (thermomechanical analysis).

[0057] Figure 8 This is the thermogravimetric analysis test result of the phenyl-containing polyvinylcyclohexane derivative TVCH-BP-TVCH of Example 2 of the present invention. DETAILED DESCRIPTION

[0058] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0059] Example 1

[0060] The preparation reaction formula of the aromatic-containing polyvinyl cyclohexane derivative of this embodiment is as follows:

[0061]

[0062] The raw materials used are: trivinylcyclohexane (8 mmol, molecular weight 162, 1.296 g), p-dibromobenzene (4 mmol, molecular weight 236, 0.944 g), palladium acetate (0.018 mmol, molecular weight 224.5, 8.08 mg, 0.9 mol% of bromobenzene), potassium phosphate (11.2 mmol, molecular weight 212, 2.37 g), triphenylphosphine (0.024 mmol, molecular weight 262, 6.3 mg), and 8 ml of N,N-dimethylformamide (DMF).

[0063] The operation process is as follows: add 2.37 grams of potassium phosphate, 6.3 milligrams of triphenylphosphine (molecular weight 262), 1.29 grams of trivinylcyclohexane (8 mmol), 0.94 grams of 1,4-dibromobenzene (4 mmol), 8.08 milligrams of palladium acetate (0.018 mmol), 8 milliliters of DMF into a flask, change to argon atmosphere, and react at 140 degrees for 48 hours. Add water to precipitate the product, extract the product with 40 ml of toluene, centrifuge to obtain a toluene solution, dry it with anhydrous magnesium sulfate, quickly pass it through a toluene silica gel column, spin dry, and drain the toluene with a 120-degree electric heating jacket oil pump to obtain a viscous yellow-red substance, recrystallize it with 8 ml of methanol overnight, pour out the methanol, and place it in a vacuum drying oven at 80°C with a diaphragm pump for one hour. Finally, 1.325 g of the product is obtained, with a yield of 82.8%; its main component is TVCH-Ph-TVCH, which contains a small amount of oligomers, which does not affect the use.

[0064] The NMR spectrum of the phenyl-containing polyvinylcyclohexane derivative TVCH-Ph-TVCH of this example is as follows: Figure 1 shown.

[0065] The above-mentioned phenyl-containing polyvinyl cyclohexane derivative TVCH-Ph-TVCH and 1% diisopropylbenzene peroxide were placed in a test tube and heated to 220°C under nitrogen for 2 hours to obtain a cross-linked polyvinyl cyclohexane derivative. A small amount of the cured sample was subjected to thermogravimetric analysis. The results were as follows: Figure 4 As shown, 5% thermal weight loss is at 327°C, and 10% thermal weight loss is at 410°C.

[0066] The preparation of the copper clad laminate for high frequency circuit of this embodiment is as follows:

[0067] 30 g of hydrogenated styrene-butadiene-styrene copolymer (SEBS), 70 g of phenyl-containing polyvinylcyclohexane derivative TVCH-Ph-TVCH, 20 g of silica powder and 1 g of diisopropylbenzene peroxide (DCP) were added to 300 ml of toluene and stirred at room temperature until completely dissolved.

[0068] The surface-modified glass fiber cloth (10 cm × 10 cm) was immersed in the organic medium slurry prepared above until it was coated by the organic medium slurry; then, it was air-dried at 80°C for 15 minutes until the surface was dry. 2 to 10 layers of glass fiber cloth prepreg were placed between two layers of copper foil and put into a hot press. The prepreg was pressed at 210°C and a pressure of 10 MPa for 2 hours. Finally, the hot-pressed laminate was cooled to room temperature to obtain a copper clad laminate sample.

[0069] The copper clad laminate samples were cut into standard samples for thermal stability analysis. The Tg glass transition temperature of the single cantilever test by DMA (dynamic thermal mechanical analysis) was 277°C. Figure 2 shown.

[0070] After the copper clad laminate samples were cut into standard samples, thermal stability analysis was performed. The Tg glass transition temperature tested by TMA (thermomechanical analysis) was 260°C, and the thermal expansion coefficient CTE was 260ppm / °C. Figure 3 shown.

[0071] Example 2

[0072] The preparation reaction formula of the aromatic-containing polyvinyl cyclohexane derivative of this embodiment is as follows:

[0073]

[0074] The operation process is as follows: add 2.37 grams of potassium phosphate, 6.3 milligrams of triphenylphosphine, 1.29 grams of trivinylcyclohexane (8mmol), 1.25 grams of 4,4-dibromobiphenyl (4mmol), 8.08 milligrams of palladium acetate (0.018mmol), 8 milliliters of DMF into a flask, change to argon atmosphere, and react at 140 degrees for 48 hours. Add water to precipitate the product, extract the product with 40ml of toluene, centrifuge to obtain a toluene solution, dry it with anhydrous magnesium sulfate, quickly pass it through a toluene silica gel column, spin dry and drain the toluene with a 120-degree electric heating jacket oil pump to obtain a viscous yellow-red substance, recrystallize it with 8ml of methanol overnight, pour out the methanol, and place it in a vacuum drying oven at 80℃ with a diaphragm pump for one hour. Finally, 1.6328g is obtained, with a yield of 85.98%. Its main component is TVCH-BP-TVCH, which contains a small amount of oligomers that do not affect its use. The NMR spectrum of the phenyl-containing polyvinylcyclohexane derivative TVCH-BP-TVCH of this example is shown in Figure 5 .

[0075] The polyvinyl cyclohexane derivative TVCH-BP-TVCH and 1% diisopropylbenzene peroxide were placed in a test tube and heated to 220°C under nitrogen atmosphere for 2 hours to obtain a cross-linked polyvinyl cyclohexane derivative. A small amount of the cured sample was subjected to thermogravimetric analysis. The results were as follows: Figure 8 As shown, 5% thermal weight loss is at 425°C, and 10% thermal weight loss is at 448°C.

[0076] The preparation of the copper clad laminate for high frequency circuit of this embodiment is as follows:

[0077] 30 g of hydrogenated styrene-butadiene-styrene copolymer (SEBS), 70 g of biphenyl-containing polyvinylcyclohexane derivative TVCH-BP-TVCH, 20 g of silica powder and 1 g of diisopropylbenzene peroxide (DCP) were added to 300 ml of toluene and stirred at room temperature until completely dissolved.

[0078] The surface-modified glass fiber cloth (10 cm × 10 cm) was immersed in the organic medium slurry prepared above until it was coated by the organic medium slurry; then, it was air-dried at 80°C for 15 minutes until the surface was dry. 2 to 10 layers of glass fiber cloth prepreg were placed between two layers of copper foil and put into a hot press. The prepreg was pressed at 210°C and a pressure of 10 MPa for 2 hours. Finally, the hot-pressed laminate was cooled to room temperature to obtain a copper clad laminate sample.

[0079] The copper clad laminate samples were cut into standard samples for thermal stability analysis. The Tg glass transition temperature of the single cantilever test by DMA (dynamic thermal mechanical analysis) was 271°C. Figure 6 shown.

[0080] The copper clad laminate samples were cut into standard samples for thermal stability analysis. The TMA (thermomechanical analysis) test is shown in the attached Figure 7 shown.

[0081] The test results of peel strength, thermogravimetric (Tg), thermal expansion coefficient, dielectric loss at 10 GHz (Df), dielectric constant at 10 GHz (Dk), and storage modulus of the copper clad laminate sample prepared in this embodiment are shown in Table 1.

[0082] Comparative Example

[0083] The organic dielectric slurry is prepared using the best low dielectric hydrocarbon resin, diphenylethylene ethane (BVPE). The structure of diphenylethylene ethane is as follows:

[0084]

[0085] The preparation of the copper clad laminate for high frequency circuit of this comparative example is as follows:

[0086] 30 g of hydrogenated styrene-butadiene-styrene copolymer (SEBS), 70 g of biphenylethylene ethane (BVPE), 20 g of silica powder and 1 g of dicumyl peroxide (DCP) were added to 300 ml of toluene and stirred at room temperature until completely dissolved.

[0087] The surface-modified glass fiber cloth (10 cm × 10 cm) was immersed in the slurry prepared above until it was coated with the solution; then, it was dried by air blast at 80°C for 15 minutes until the surface was dry. 2 to 10 layers of glass fiber cloth prepreg were placed between two layers of copper foil and put into a hot press. The prepreg was pressed at 210°C and a pressure of 10 MPa for 2 hours. Finally, the hot-pressed laminate was cooled to room temperature to obtain a copper clad laminate sample.

[0088] The peel strength, thermal gravity (Tg), thermal expansion coefficient, dielectric loss at 10 GHz (Df), dielectric constant at 10 GHz (Dk), and storage modulus test results of the copper clad laminate samples prepared in this comparative example are shown in Table 1.

[0089] Table 1 Comparison of performance of copper clad laminate samples of Examples 1 to 2 and Comparative Examples

[0090]

[0091] It can be seen from Table 1 that compared with BVPE, TVCH-Ph-TVCH and TVCH-BP-TVCH have higher glass transition temperatures, which can be seen from the test results of dynamic mechanical analysis DMA. The glass transition temperatures Tg of BVPE, TVCH-Ph-TVCH and TVCH-BP-TVCH obtained by the single cantilever method are 190.55℃, 277.58℃, and 271.04℃, respectively, while the glass transition temperatures Tg obtained by the three-point bending method are 167.93℃, 246.17℃, and 246.77℃, respectively.

[0092] From Table 1, we can see that although the dielectric loss Df of TVCH-Ph-TVCH and TVCH-BP-TVCH is not as low as that of BVPE, their stability is very high. For example, TVCH-Ph-TVCH is immediately measured as 0.00101, but its stability is higher, 0.00105 after 1 hour, and still 0.00105 after 24 hours, that is, the dielectric loss only increases by 4% after 1 hour, and there is no change from 1 to 24 hours, while the dielectric loss of diphenylethylene BVPE with the best performance at present increases by 6.3% after 1 hour, and continues to increase by 7.6% from 1 to 24 hours, with a total increase of 13.9%.

[0093] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a copper-clad laminate for a high-frequency circuit, characterized in that: The following steps are involved: 25-35 parts of hydrogenated styrene-butadiene-styrene copolymer, 65-75 parts of aromatic-containing polyvinyl cyclohexane derivatives, 15-25 parts of silicon dioxide powder, and 0.8-1.2 parts of dicumyl peroxide are added to an organic solvent and stirred until completely dissolved to obtain an organic medium slurry; soaking the glass fiber cloth in the organic medium slurry until the glass fiber cloth is covered by the organic medium slurry to obtain the glass fiber cloth prepreg; Multiple layers of glass fiber cloth prepreg are placed between two layers of copper foil, and after hot pressing, a copper clad laminate for high-frequency circuits is obtained; Wherein, the aromatic-containing polyvinyl cyclohexane derivative has the following structure: wherein Ar is an aromatic hydrocarbon; TVCH is triethylene cyclohexane, and its structure is one of the following structures: TVCH is connected to the aromatic hydrocarbon at the dotted line.

2. The method for preparing a copper clad laminate for high-frequency circuits according to claim 1, characterized in that: The aromatic hydrocarbon is benzene, biphenyl, terphenyl, fluorene, naphthalene or anthracene.

3. The method for preparing a copper clad laminate for high frequency circuits according to claim 1, characterized in that: The aromatic hydrocarbon has one of the following structures:

4. The method for preparing a copper clad laminate for high frequency circuits according to claim 1, characterized in that: The preparation of the aromatic-containing polyvinyl cyclohexane derivative is as follows: Potassium phosphate, 1,2,4-trivinylcyclohexane, dibromoaromatic hydrocarbons, N,N-dimethylformamide, palladium acetate and triphenylphosphine are added; the reaction is carried out at 120-140° C. for 20-48 hours in an argon atmosphere; the product is precipitated, centrifuged, dried, column-passed, spin-dried and pumped dry with an oil pump heated to 115-125° C., then recrystallized, and pumped with a diaphragm pump at 75-85° C. in a vacuum drying oven for 0.8-1.2 hours to obtain a polyvinylcyclohexane derivative containing an aromatic group.

5. The method for preparing a copper clad laminate for high frequency circuits according to claim 4, characterized in that: The molar ratio of the 1,2,4-trivinylcyclohexane to the dibromoarene is (1.8-2.2):

1.

6. The method for preparing a copper clad laminate for high frequency circuits according to claim 4, characterized in that: The added amount of palladium acetate is 0.8-1.0% of the molar amount of dibromoarene; the added amount of triphenylphosphine is 1%-5% of the molar amount of dibromoarene.

7. The method for preparing a copper clad laminate for high frequency circuits according to claim 1, characterized in that: The hot pressing is specifically: hot pressing under the conditions of 205-215° C. and 2.8-3.2 MPa.

8. A copper-clad laminate for high-frequency circuits, characterized in that: The copper-clad laminate is prepared by the method for preparing a copper-clad laminate for high-frequency circuits according to any one of claims 1 to 7.

9. Organic medium slurry, characterized in that By weight, it comprises the following components dissolved in an organic solvent: The aromatic-containing polyvinyl cyclohexane derivative has the following structure: wherein Ar is an aromatic hydrocarbon; TVCH is triethylene cyclohexane, and its structure is one of the following structures: TVCH is connected to the aromatic hydrocarbon at the dotted line.

10. A polyvinylcyclohexane derivative containing an aromatic group, characterized in that: Has the following structure: wherein Ar is an aromatic hydrocarbon; TVCH is triethylene cyclohexane, and its structure is one of the following structures: TVCH is connected to the aromatic hydrocarbon at the dotted line.

Citation Information

Patent Citations

  • Low-dielectric polyperfluorinated ethylene propylene copper-clad plate and preparation method thereof

    CN110228239A

  • Benzocyclobutene substituted triethylene cyclohexane compound and preparation method thereof, organic dielectric material and preparation method thereof

    CN114478178A

  • Resin composition and prepreg and copper-clad laminate manufactured by using same

    CN118271535A